Feasibility and safety of reduced-port video-assisted thoracoscopic surgery using a needle scope for pulmonary lobectomy– retrospective study. (September 2019) - Aragaki, Masato; Kaga, Kichizo; Hida, Yasuhiro; Kato, Tatsuya; Matsui, Yoshiro
Abstract: Background: This study aimed to determine the usefulness and limitations of videoassisted thoracoscopic (VATS) lobectomy using one-window and puncture method (1WPM). Methods: This study involved 14 patients who underwent lobectomy using the 1WPM at our institute from 2008 to 2017. Results: The study patients comprised of 3 men and 11 women with a median age of 10.5 years (range, 0-72 years). There were eight cases in children younger than 18 years old and the youngest patient was 9 days old. The diagnoses were congenital pulmonary cystic disease (n = 7), primary lung cancer (n = 4), metastatic lung tumor (n = 1), and others (n = 2). The 1WPM was successful in 9 of 14 patients (64.3%) and, in 5 cases (35.7%), needed conversion to either two-window method (TWM) using additional port (n = 3) or open thoracotomy (n = 2). The causes for conversion were need for additional bronchoplasty or lymph node dissection (n = 3), failure of one-lung ventilation (n = 1), and presence of a small thoracic cavity that made the procedure extremely difficult (n = 1). In the group that was successfully treated with 1WPM, the median values were as follows: operation time, 193 min (range, 112-480 min); blood loss, 0 ml (range, 0-90 ml); drainage duration, 1 day (range, 1-4 days); and postoperative hospital stay, 7 days (range, 4-13 days). Conclusions: Lobectomy by 1WPM can be safely performed and has good postoperative course and this procedure can be applicable and effective in small infants. Highlights: This study describes the novel VATS lobectomy method: the one-window and puncture method (1WPM). 1WPM is performed using 2–3 cm single incisions and a needle scope for intrathoracic access from other points. This retrospective study involved 14 patients who underwent lobectomy using the 1WPM. VATS lobectomy using 1WPM can be safely applied from adult cases to new born cases.